A randomised, open-labelstudy of insulin glargine or neutral protamine Hagedorn insulin in Chinese paediatric patients with type 1 diabetes mellitus. Issue 1 (December 2016) - Liu, Min; Zhou, Zhiguang; Yan, Jinhua; Li, Pin; Song, Wenhui; Fu, Junfen; Chen, Xiaobo; Zhao, Weigang; Xi, Li; Luo, Xiaoping; Sha, Liang; Deng, Xueyuan; et al.
Abstract Background We aimed to describe the safety and efficacy of insulin glargine in Chinese paediatric patients with type 1 diabetes mellitus (T1DM). Neutral protamine Hagedorn (NPH) insulin was the reference therapy. Methods This open-label, randomised, Phase III study was conducted at 10 sites in China. Children aged ≥6 to <18 years with T1DM were randomised (2:1) to insulin glargine or NPH insulin asbasal insulinfor a 24-week treatment period. For all patients, insulin aspart was given as bolus insulin. The primary endpoint was absolute change in glycated haemoglobin(HbA1c) from baseline to Week 24. Secondary endpoints included the percentage of patients reaching HbA1c <7.5% (<58.5 mmol/mol), and safety. The study was registered at clinicaltrials.gov (NCT01223131). Results In total, 196 patients were screened, and 162 were randomised (107 and 55 patients were randomised to insulin glargine and NPH insulin, respectively). The mean ± SD of absolute change in HbA1c was–0.25 ± 1.68% (–2.69 ± 18.32 mmol/mol) in the insulin glargine group and –0.54 ± 1.67% (–5.55 ± 20.32 mmol/mol) in the NPH insulin group. At Week 24, 18.7 and 21.6% of patients in the insulin glargine and NPH insulin groups achieved HbA1c <7.5% (<58.5 mmol/mol). Both treatments were generally well tolerated. A numerically lower rate of symptomatic hypoglycaemia per patient year was observed for insulin glargine versus NPH insulin (24.3 ± 45.8 versus32.3 ± 43.2); severe hypoglycaemia was rare (<2%). Conclusions Initiation of insulin glargine can aid Chinese paediatric patients with T1DM to safely reduce their HbA1c levels.